Scan direction influences explicit but not implicit perception of a goalkeeper`s position - Noël, B.; van der Kamp, J.; Masters, R. (Attention, Perception, & Psychophysics, 2016)
In soccer penalty kicking, it has been demonstrated that systematic biases in a penalty taker`s explicit perception of the goalkeeper`s position do not always show up in decisions about the side to which to kick. To scrutinize whether this off-center effect is a function of dissociations between explicit and implicit perception of the goalkeeper`s position, we examined to what degree visual scan direction affects explicit as well as implicit perception of goalkeeper position. To this end, participants were presented with pictures of a goalkeeper who stood at different (marginal) distances to the right or left of goal center. To manipulate scan direction, participants fixated the right, middle, or left of the scene at the beginning of each trial. They were instructed only to kick the ball if they perceived the goalkeeper to be standing in the center of the goal. Results showed that scan direction systematically influenced explicit perception of goalkeeper position (i.e., the decision to kick). Yet, if participants decided to kick (and thus believed that the goalkeeper stood in the true center), then the kicks were more often directed to the side with more space (i.e., 64.1 %) irrespective of scan direction. These findings provide further evidence that the off-center effect arises from dissociations between explicit and implicit perception of goalkeeper position, with the former but not the latter being susceptible to attentional asymmetries.